Pelaksanaan Perjanjian Lisan dalam Praktek Sewa Menyewa Rumah Menurut Hukum Positif Indonesia Di Desa Jati Sidoarjo - Sabrina Wini Nurlita (Jurnal Syntax Transformation, 2021)
This study discusses the implementation of oral agreements on renting houses according to Indonesia's positive laws. The type of research used in this study is juridical empirical. By using sources - data sources that are the results of research, books - books literature and legislation - applicable legislation. In this study, using qualitative data analysis method by collecting data that is then processed into a research result. The results of the study can be concluded that the implementation of renting a house that is done by the community is still widely used the system of verbal agreements. The oral agreement begins at the time of an agreement between the two parties. Negligence and willfulness caused by one party that causes harm to the other party. This causes many problems that arise as a result of the implementation of the lease agreement verbally.